Genetic association and bidirectional Mendelian randomization for causality between gut microbiota and six lung diseases - Su, Yue; Zhang, Youqian; Xu, Jinfu (Frontiers in Medicine, 2023)
Purposes Increasing evidence suggests that intestinal microbiota correlates with the pathological processes of many lung diseases. This study aimed to investigate the causality of gut microbiota and lung diseases. Methods Genetic information on intestinal flora and lung diseases [asthma, chronic bronchitis, chronic obstructive pulmonary disease (COPD), interstitial lung disease (ILD), lower respiratory tract infection (LRTI), pulmonary arterial hypertension (PAH)] and lung function was obtained from UK Biobank, FinnGen, and additional studies. A Mendelian randomization (MR) analysis was conducted to explore the causal association between gut microbiota and lung diseases. Results The genetic liability to lung diseases may be associated with the abundance of certain microbiota taxa. Specifically, the genus Prevotella (p = 0.041) was related to a higher risk of asthma; the family Defluviitaleaceae (p = 0.002) and its child taxon were identified as a risk factor for chronic bronchitis; the abundance of the genus Prevotella (p = 0.020) was related to a higher risk of ILD; the family Coriobacteriaceae (p = 0.011) was identified to have a positive effect on the risk of LRTI; the genus Lactobacillus (p = 0.0297) has been identified to be associated with an increased risk of PAH, whereas the genus Holdemanella (p = 0.0154) presented a causal decrease in COPD risk; the order Selenomonadales was identified to have a positive effect on the risk of FEV1(p = 0.011). The reverse TSMR analysis also provided genetic evidence of reverse causality from lung diseases to the gut microbiota. Conclusion This data-driven MR analysis revealed that gut microbiota was causally associated with lung diseases, providing genetic evidence for further mechanistic and clinical studies to understand the crosstalk between gut microbiota and lung diseases.